Aromatic hydrocarbons provide new insight into carbonate concretion formation and the impact of eogenesis on organic matter - Plet, Chloe; Grice, Kliti; Scarlett, Alan; Ruebsam, W.; Holman, Alex; Schwark, Lorenz (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Investigations of aromatic biomarkers extracted from carbonate concretions can contribute to characterization of the enhanced microbial activity that mediates carbonate concretion formation. This microbial footprint can be further inferred from the stable isotopic values of carbonate (δ13C) and pyrite (δ34S). Here, we used a combination of GC–MS and GC × GC-ToF-MS to compare the aromatic fractions of two Toarcian carbonate concretions from the H. falciferum ammonite zone of the Posidonia Shale (SW-Germany) and their host sediment. The results revealed that n-alkylated and phytanyl arenes were enhanced in the concretions, relative to the host sediment. These findings support a very early diagenetic (eogenetic) microbial source for alkylated and phytanyl arenes derived from the microbial ecosystem mediating concretion formation. In contrast, aromatic compounds formed by thermal maturation (e.g. polycyclic aromatic hydrocarbons, aromatic steroids, organic sulphur compounds) remained invariant in host rock and concretion samples. When combined with bulk sediment and concretion properties, the distribution of aromatic compounds indicates that eogenetic microbial activity upon concretion growth does not diminish organic matter quality.